2010
DOI: 10.3354/meps08832
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and growth of Scomber japonicus and S. australasicus larvae in the southern East China Sea in response to oceanographic conditions

Abstract: Chub mackerel Scomber japonicus and spotted mackerel S. australasicus are important fishery resources in the countries adjacent to the East China Sea (ECS). During February to March in 2004 and 2005, based on species identification using PCR-restriction fragment length polymorphism (PCR-RFLP) analysis of mtDNA, we examined the larval distribution, transport and growth of both species in the southern ECS, where extremely high abundances of Scomber spp. larvae are found. Distribution of S. australasicus was in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…, 2004) or the transport and dispersal of larvae (Franco‐Gordo et al. , 2003; Sassa and Tsukamoto, 2010) of the different species, other oceanographic variables also affected the distribution pattern of larval fish. Most research on larval fish assemblage in different regions of the world has shown the influences of bathymetry and spawning grounds of adults on the spatial distribution patterns (Olivar, 1990; Muhling et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2004) or the transport and dispersal of larvae (Franco‐Gordo et al. , 2003; Sassa and Tsukamoto, 2010) of the different species, other oceanographic variables also affected the distribution pattern of larval fish. Most research on larval fish assemblage in different regions of the world has shown the influences of bathymetry and spawning grounds of adults on the spatial distribution patterns (Olivar, 1990; Muhling et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kuroshio Branch Current, and South China Sea Surface Current were detected between seasons. With the ordination analysis of the dominant taxa (CCA diagram), we found that the abundances of most dominant species were closely related to the abundance of chlorophyll a and zooplankton, indicating that in addition to the importance of seasonality in regulating community structure by the reproduction periods (Gray and Miskiewicz, 2000;Koutrakis et al, 2004) or the transport and dispersal of larvae (Franco-Gordo et al, 2003;Sassa and Tsukamoto, 2010) of the different species, other oceanographic variables also affected the distribution pattern of larval fish. Most research on larval fish assemblage in different regions of the world has shown the influences of bathymetry and spawning grounds of adults on the spatial distribution patterns (Olivar, 1990;Muhling et al, 2007).…”
Section: Biological Processes Controlling Larval Fish Distributionmentioning
confidence: 98%
“…In contrast, directly investigating the spatial and temporal distributions of fish eggs and larvae is an ideal alternative. Since diverse fish eggs and larvae can be captured through zooplankton net sampling, researchers can more easily and precisely identify the spawning and nursery grounds and the spawning period through ichtyoplankton assessments (Sassa and Tsukamoto, 2010;Ellis et al, 2012;Hsieh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of S. japonicus start to appear from March off Jeju Islands (Yoo 1991). These larvae could be transported by the Kuroshio Currents at the end of February or in the beginning of the March from the northern seas of Taiwan in the South China Sea (Sassa and Tsukamoto 2010). However, the main stream of the Kuroshio Current does not directly flowing into the Korean coastal seas.…”
Section: Resultsmentioning
confidence: 99%